(3GdEQTGO aj GdJhMjOs - (3YHO Gdedc Hf YHO Gddg Hf jhSa Hf eMeO GdLhjfj, CHh GdeYGdj, Qcf GdOjf, GdedbH HEeGe GdMQejf,J (B478 (3g` s
(3ChdgG (B:s
(3aEf GdbOQI YfOge dGJDKQ ai GjbGY GdebOhQ TGgOkG s
(3BNQgG (B:s
(3hGdGNHGQ GdhGQOI ai aVGFdge eYGQVI hdGjecf hcdeG jMGhdhf EKHGJ YUeI GdGeGe hGdMeO ddg QH GdYGdejf Je cJGH GdGQTGO s
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B70s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd s
Keywords: (3CUhd Gdabgs